2022
DOI: 10.1002/smll.202108092
|View full text |Cite
|
Sign up to set email alerts
|

Introducing the Solvent Co‐Intercalation Mechanism for Hard Carbon with Ultrafast Sodium Storage

Abstract: et al. [13] found that the platform capacity of ball-milled carbon materials dropped sharply, which is consistent with graphite structural collapse in LIBs. Sun et al. [14,15] also proved the existence of an insertion reaction through in situ XRD experiments. Although a lot of studies have proven this model, some experimental phenomena still cannot be explained. Recently, Atsuo Yamada et al. [16] have explored in detail the sodium storage process of hard carbon by combining ex situ small and wide-angle X-ray s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 35 publications
1
19
0
Order By: Relevance
“…In this stage, the kinetic bottleneck lies on the Na + diffusion between the graphitic layers, and a wider graphitic layer spacing favors the fast Na + diffusion. [ 35,36 ] Recently, Wu et al found that the solvent cointercalation mechanism of hard carbon in ether electrolytes can lead to an increase in the interlayer spacing of hard carbon, which in turn results in the significant improvement of sodium ion diffusion and kinetic performance, this result was consistent with the earlier analysis. [ 37 ] Besides, compounding hard carbon with other sodium storage materials with fast Na + diffusion may also improve its kinetic performance.…”
Section: Resultssupporting
confidence: 80%
“…In this stage, the kinetic bottleneck lies on the Na + diffusion between the graphitic layers, and a wider graphitic layer spacing favors the fast Na + diffusion. [ 35,36 ] Recently, Wu et al found that the solvent cointercalation mechanism of hard carbon in ether electrolytes can lead to an increase in the interlayer spacing of hard carbon, which in turn results in the significant improvement of sodium ion diffusion and kinetic performance, this result was consistent with the earlier analysis. [ 37 ] Besides, compounding hard carbon with other sodium storage materials with fast Na + diffusion may also improve its kinetic performance.…”
Section: Resultssupporting
confidence: 80%
“…Figure 6g,h and Figure S18 (Supporting Information) exhibit galvanostatic intermittent titration technique (GITT) potential profiles with a pulse current of 0.05 A g −1 for 0.5 h ( τ ), followed by a 1.0 h relaxation process and Na + diffusion coefficients calculated from Equation () [ 29–30,37,43 ] : DNa+badbreak=4πτmBVmMBnormalS2normalΔESnormalΔEτ2,τgoodbreak≪L2/DNa+$$\begin{equation}{{\rm{D}}}_{{\rm{Na}}^{\rm{ + }}}{\rm{ = }}\frac{{\rm{4}}}{{{\rm{\pi \tau }}}}{\left( {\frac{{{{\rm{m}}}_{\rm{B}} V_{\rm{m}}}}{{{{\rm{M}}}_{\rm{B}}{\rm{S}}}}} \right)}^{\rm{2}}{\left( {\frac{{\Delta {{\rm{E}}}_{\rm{S}}}}{{\Delta {{\rm{E}}}_{{\tau}}}}} \right)}^{\rm{2}}{\rm{,\tau }} \ll {{\rm{L}}}^{\rm{2}}{\rm{/}}{{\rm{D}}}_{{\rm{Na}}^{\rm{ + }}}\end{equation}$$…”
Section: Resultsmentioning
confidence: 99%
“…3a, a strong broad characteristic peak located at about 211 is found in the XRD patterns of all Se-HMC samples, which belongs to the (002) crystalline plane of carbon materials. 30 In general, carbon materials with regular graphitic layers have sharp (002) peaks, while amorphous carbons with disordered carbon layers exhibit broad (002) peaks. It is clear that the Se-HMC samples are typical amorphous carbons.…”
Section: Resultsmentioning
confidence: 99%